LA SABIDURÍA Y EL ARTE DE VIVIR EN OCTAVO CURSO. EXPERIENCIAS DE LOS MAESTROS DEL PROYECTO “PHILOSOPHIZING THE DIALOGOS WAY” - Helskog, Guro Hansen; Weiss, Michael Noah (Revista Internacional de Filosofía Aplicada HASER, 2021)
This paper discusses teachers` self-reported experiences from participating in a Dialogos philosophizing project over five months, from the perspective of wisdom development. The project involved teachers from 13 upper secondary schools in a municipality in Scandinavia. They were given a course on philosophy and rhetoric over four workshops with five weeks in between. Moreover, they were themselves supposed to facilitate 20 philosophical dialogue sessions with their own 8th grade students during the project. The research methods used were participative observation and analysis of teachers` meta-reflection notes after the last workshop. The paper concludes with that the project did seem to enhance teachers`wisdom. According to the teachers, the students had also become much more reflected due to the project.